New insights into the tumor immune microenvironment and immunotherapy of thyroid cancer - Du, Jia-jia; Wang, Jian; Ma, Kai; Ma, Peng (Frontiers in Immunology, 2026)
Thyroid cancer (TC) is the most common malignant tumor of the endocrine system. Although most cases have a favorable prognosis, some patients may be resistant to treatment or exhibit aggressive behavior. The tumor microenvironment (TME) network, composed of stromal cells, immune cells, vascular cells, and cancer cells, has become a key factor in the development of TC. The TME affects the biological behavior of TC through different immune states. TC cells can suppress antitumor immune response by promoting an immunosuppressive microenvironment, such as through the recruitment of tumor-associated macrophages (TAMs), tumor-associated mast cells (TAMCs), myeloid-derived suppressor cells (MDSCs), tumor-associated neutrophils (TANs), and regulatory T cells (Tregs), among other immunosuppressive cells. They also express negative immune checkpoints such as programmed death ligand 1 (PD-L1) and cytotoxic T lymphocyte-associated protein 4 (CTLA-4), and immunosuppressive enzymes such as indoleamine 2,3-dioxygenase 1 (IDO1). This suggests that immunotherapy may be a promising treatment for TC, especially for patients who do not respond to traditional therapies. This article focuses on the interaction mechanism of cells and molecules in the tumor immune microenvironment (TiME) involved in the occurrence and development of TC and analyzes its potential value as a therapeutic target. In addition, the latest clinical trials related to immunotherapy for TC are summarized.